The effect of audit quality and capital intensity ratio on earning management in sharia listed companies - Siti Aisyah; Muhammad Asmeldi Firman; Rianti Pratiwi (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Purpose - This study aims to determine the effect of audit quality and capital intensity ratio on earnings management in companies listed on the Indonesia Sharia Stock Index in 2017-2020.Method - This study is quantitative research using secondary data obtained from the summary of audited financial statements. Data sampling was selected by purposive sampling method based on certain criteria. The analysis technique used is multiple linear regression.Result - The results show that the size of the public accounting firm has a negative effect on earnings management; it is more credibility consideration. The audit tenure has a positive effect on earnings management. It creates an emotional connection that is reluctance to disclose misappropriation. The auditor industry specialization has a negative effect on earnings management; it is more in-depth various accounting policies to find earnings management. The capital intensity ratio does not affect earning management; it is business and finance consideration. Accounting policies in depreciation is carry out when management has decided to invest in fixed assets.Implication - Sharia companies should pay attention to audit quality and capital intensity ratios in relation to earnings management.Originality - This is a study to test the existence of earnings management in Sharia companies in terms of audit quality and capital intensity ratio factors.